Gender perspectives of globalization and human development: Evidence from individual-level data - Jayanti Behera; Dukhabandhu Sahoo (Research in Globalization)
Global development debate, which challenges the traditional North-South divide and focuses on the within-country or micro-level development perspective, argues that there is gender inequality in development within countries or at the micro level. It has brought a new dimension to the argument on development issues by addressing the gender perspective of globalization. Globalization plays a vital role in contributing to greater gender equality in human development. In view of this, this study explores the gender dynamics of globalization and human development at the individual level by covering geo-socioeconomic factors in Odisha, India. It uses primary data collected through a structured survey schedule from 579 individuals in Odisha. By using the beta regression model, the study found that both sociocultural and environmental globalization improve human development at the individual level. Further, as regards the gender perspective, the effect of environmental globalization on human development is stronger for females than males. However, the effect of psychological globalization on human development is weaker for females than for males. Females have lower levels of human development than males, while adults and middle-aged individuals have higher levels of human development than elderly individuals. Moreover, individuals from other backward classes, scheduled classes, and scheduled tribes have lower levels of human development than individuals from unreserved categories. Individuals from Muslim and Christian communities have higher levels of human development than those from Hindu communities. Individuals from joint families experience higher levels of human development than those from nuclear families. Additionally, urban residents have higher levels of human development than rural ones, while individuals from tribal regions have lower levels of it than those from nontribal ones. In order to promote gender equality, globalization can be used as a tool for female human development, having special provisions for female members of the state.